(untitled) (Research, Society and Development, 2023)
Over the Years, the deaf Community has occupied more and more Spaces and Much has been said about inclusion, whether it be people with hearing impairments or other groups that really need this movement. However, it should be noted how Much these different physical and social Spaces have actually promoted inclusion. Therefore, looking at the field of Civil Engineering, with emphasis on academic training, it is Worth analyzing how this inclusion has occurred, if it actually occurs and how it occurs. Thus, this research aimed to carry out a bibliographic survey in scientific journals and annals of events related to Civil Engineering, aiming at the quantification and analysis of publications that are aimed at the deaf public or the hearing impaired in Brazil. A comparison of advances and achievements of the deaf Community was carried out, promoting a discussion about how civil engineering has accompanied (or not) these advances. It is concluded from the data that, although a few Steps have been taken towards the inclusion of deaf people in the area, there is still Much to be developed, such as the elaboration of signs of technical terms in the Brazilian Sign Language and the promotion of didactic strategies to better reach deaf people during initial training in Civil Engineering.